THE EFFECTIVENESS OF GEOGEBRA-BASED VAN HIELE MODEL ON MATHEMATICAL DISPOSITION ASSESSED FROM EARLY MATHEMATICS ABILITY - Widyah Noviana; Windia Hadi; Ita Handayani (KALAMATIKA Jurnal Pendidikan Matematika, 2020)
The aim of this research was to observe the effectiveness of geogebra based van hiele model on mathematical disposition assessed from early mathematics ability. The accessible population of the present study was students of Prof. DR. HAMKA Muhammadiyah University. Samples of this research is semester two students from mathematics education program. Due to the happening Covid-19 pandemic, the present study was conducted online. The method employed was quasi-experiment using factorial treatment by level 2 × 2 design. The data were collected with mathematical disposition questionnaire and early mathematics ability instrument. After the data were collected, they were then analyzed with two-way ANAVA analysis. The result showed that there was no significant difference in the increase mathematical disposition of students who are given the learning model and early mathematics ability. The conclusion obtained is that the geogebra based Van Hiele Model is ineffective on students’ mathematical disposition in terms of their early mathematics abilitiy. This is due to several factors, namely internal factors and external factors. The internal factors are decreas in the score of mathematical disposition from pretest to posttest, lack of understanding applying geogebra software with online learning. External factors are quotas and poor internet network.